2011
DOI: 10.1080/15022250.2011.593365
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Worries after Terrorist Attacks: Report from a Field Experiment

Abstract: The current study reports the results of a field experiment measuring tourist worries assessed by the Tourist Worry Scale (TWS) before and after the terror bombings in London during the summer of 2005. As part of a larger study on tourist experiences, tourists on vacation to Mallorca, Spain, were asked to fill in a questionnaire prior to the bombings. A follow up study was administered about seven weeks after the terror attacks. The results showed sum scores on the TWS to remain stable over the test period, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Future research could look at the ecological validity of the present findings. Still, results of field studies reported by Larsen et al (2011), andBrun et al (2011) do seem to support the ecological validity of the current investigation.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Future research could look at the ecological validity of the present findings. Still, results of field studies reported by Larsen et al (2011), andBrun et al (2011) do seem to support the ecological validity of the current investigation.…”
Section: Discussionmentioning
confidence: 55%
“…However, in countries where terrorism is organized but relatively infrequent, increased risk perceptions and worry after a terror attack are to be expected. As discussed above, this is what Larsen et al (2011) and Brun et al (2011) reported after the terror attacks in Madrid andLondon in 2004 and2005. The most recent events with such characteristics (that is infrequent but organized terrorism) are the terror attack at Charlie Hebdo in Paris in January 2015 and the multiple and highly organized attacks in Paris in November 2015. The fact that the public's response to these attacks was so enormous while terrorism affecting far more people in other parts of the world receives relatively less attention might not only be explained by the fact that they happened in the heart of Europe.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Another interesting line of research with growing importance is loosely linked to behavioural economics and dominated by psychologists. These strands studies of the behaviour, beliefs and intentions of tourists and include studies like Doran et al (2017), Brun et al (2011), Larsen et al (2011), Larsen (2011) as well as Wolff and Larsen (2017). The study by Larsen (2007) seems to be fundamental for this research field, which, among other things, is important for the analysis of how terror and risk perceptions influence the travel intentions of tourists.…”
Section: Current State Of Tourism Economics Research In a Nordic Contextmentioning
confidence: 99%
“…Participants’ general desire to travel and risk judgments for other destinations remained unaffected. Brun, Wolff, and Larsen () found that the terrorist attacks in London and Sharm el Sheik in 2005 were associated with an increase in tourist's worries about terrorism, as well as an increase in the percentage of tourists who believed that the world had become more dangerous as a consequence of the ‘War on terror’.…”
Section: Introductionmentioning
confidence: 99%